(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2010)
F-18 FDG (2-[18-F] fluoro-2-deoxy-D-glucose) is the most frequently used radiopharmaceutical for PET and PET CT imaging exams. The FDA recently approved the use of the PTS TM (Portable Test System) as an alternative to the standard test proposed by the United States Pharmacopeia using the LAL (Limulus Amebocyte Lysates), that takes longer to perform (about 1h) than the PTS TM (15 min). Recent studies have demonstrated that radiation could interfere with the PTS TM test. In order to study the effects of radiation on the PTS TM test and/or equipment, 27 batches of F-18 FDG produced in the Nuclear Engineering Institute were analyzed. The results showed that no direct correlation with radiation was found in any of the cases.